Settings Transposition of the Scientific Elements in Hiroshi Teshigahara’s Adaptation of Kobo Abe’s the Face of Another - Anton Sutandio (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2017)
This article focuses on Hiroshi Teshigahara’s film adaptation of the famous Kobo Abe’s The Face of Another with special attention on the transposition of the scientific elements of the novel in the film. This article observes how Teshigahara, through cinematic techniques, transposes Abe’s scientific language into visual forms. Abe himself involved in the film adaptation by writing the screenplay, in which he prioritized the literary aspects over the filmic aspect. This makes the adaptation become more interesting because Teshigahara is known as a stylish filmmaker. Another noteworthy aspect is the internal dialogues domination within the novel narration. It is written in an epistolary-like narration, placing the protagonist as a single narrator which consequently raises subjectivity. The way Teshigahara externalizes the stream-of-consciousness narration-like into the medium of film is another significant topic of this essay. Keywords: transposition, scientific element, adaptation, The Face of Another